Medication management for complex patients in primary care: application of a remote, asynchronous clinical pharmacist model. Issue 7 (3rd October 2021) - Benson, Mark; Murphy, David; Hall, Lindsey; Vande Kamp, Philip; Cook, David J
ABSTRACT: Purpose : Drug therapy problems impact about one-third of US adults, and these issues are likely to continue to worsen as the population of aging Americans increases. The objective of this study is to assess the feasibility of a remotely delivered Comprehensive Medication Management (CMM) for primary practice patients who are polypharmatic and at high risk for drug therapy problems. Methods : Using medical and prescription claims data, a list of Medicare Advantage beneficiaries at high risk for drug therapy problems was identified. Participants were enrolled in a 6-month CMM program from February – November 2020. In the program, their existing drug therapy was assessed by a pharmacist, Drug therapy problems were identified and resolved. A Collaborative Practice Agreement allowed the pharmacists to make prescription changes as needed. Results : Eighty-three percent (202) of contacted individuals agreed to participate in the study. All participants were on five medications or more, and 71% were on more than eight. A clinical pharmacist found that 86% of participants had a drug therapy problem according to classification criteria. Seventy-nine percent of all drug therapy problems identified were resolved upon completion of the study. Conclusion : The findings of this study suggest that engagement of a remote clinical pharmacist can contribute to efficient resolution of most drug therapy problems identified in a primary care population. A service model using remote pharmacist services may be an effective means of improving team-based primary care medication management for this population.